Kati in Paris - Lindgren, Astrid 1907-2002; Dt. von Else v. Hollander-Lossow (Hamburg Oetinger, 2002)
Kati and her fiancé travel from Stockholm to Paris for their wedding and enough memories for their first year of marriage
Translation of: Kati i Paris
13
Keywords: Paris (France) -- Fiction